KEBIJAKAN PRESIDEN BRAZIL TERHADAP PERENCANAAN PENGEMBANGAN WILAYAH PERTANIAN DI HUTAN AMAZON YANG MENGANCAM “HUMAN SECURITY” MASYARAKAT BRAZIL - Intan Rodiah (Journal of Diplomacy and International Studies, 2019)
Amazon forest in Brazil is one of the lungs of the world and a source of oxygen, especially in the South American region. Under the leadership of President Bolsonaro, there have been many cases of forest fires and illegal deforestation due to the weakening of environmental protection in the Amazon forest region. This study wants to analyze the Brazilian president's policy towards developing agricultural areas in the Amazon forest. This paper uses a literature study writing system by taking resources from several references such as books, journals, articles, news and other sources related to the author's research. This research uses descriptive analytic method. Many things that arise due to the Amazon forest fires, especially regarding the "Human Security" of Brazilian society. Regarded as a potential area, it is not surprising that many parties who want to use the Amazon forest as a forum for agricultural activities and mining activities. With the increasing cases of forest fires in Brazil every year, it raises big questions for many parties including the community and environmental activists regarding the president's policy in tackling these fire cases. And it has also attracted the attention of some environmental observers and concerns about the impact of forest disasters that have disturbed environmental security stability and have long troubled Brazilian society, and therefore they also believe that the increase in Amazon forest fires is not only caused by natural reasons from deforestation activities only, but they assume that there is a separate mission behind this forest fire case from the Brazilian government who wants to develop agricultural area in the Amazon forest area. See this forest which has the potential to develop agricultural and mining areas.